2020
DOI: 10.1002/ca.23654
|View full text |Cite
|
Sign up to set email alerts
|

Female ejaculation: An update on anatomy, history, and controversies

Abstract: Female ejaculation is a contentious topic. From a review of the literature, history indicates that it is not a modern concept; some females were aware of it in times past without understanding the role of the fluid or composition of the ejaculate. Over time, scholars experimented, mainly with anatomical studies, in an attempt to identify the source of the ejaculate and explore its physiological and anatomical benefits for the female sexual experience. Despite these studies, views about female ejaculation remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Urea, creatinine, and uric acid in the SQ fluid confirm that it comes from the kidneys and is collected in the urinary bladder. There is no agreement on whether the biochemical composition of SQ fluid is identical to urine or is actually its diluted form (Pastor & Chmel, 2018; Rodriguez et al, 2021; Rubio‐Casillas & Jannini, 2011; Salama et al, 2015; Schubach, 2001). Two studies reported that SQ fluid is the diluted urine, (Rubio‐Casillas & Jannini, 2011; Schubach, 2001) while others assumed that it is biochemically identical with urine (Table 4) (Goldberg et al, 1983; Pastor & Chmel, 2018; Salama et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Urea, creatinine, and uric acid in the SQ fluid confirm that it comes from the kidneys and is collected in the urinary bladder. There is no agreement on whether the biochemical composition of SQ fluid is identical to urine or is actually its diluted form (Pastor & Chmel, 2018; Rodriguez et al, 2021; Rubio‐Casillas & Jannini, 2011; Salama et al, 2015; Schubach, 2001). Two studies reported that SQ fluid is the diluted urine, (Rubio‐Casillas & Jannini, 2011; Schubach, 2001) while others assumed that it is biochemically identical with urine (Table 4) (Goldberg et al, 1983; Pastor & Chmel, 2018; Salama et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…More accurately, this fluid is mainly from FE or SQ. The difference between these two terms, in terms of their similarity to urine, has been discussed (Rodriguez et al, 2021). In our opinion, the ambiguity between these two terms may unnecessarily complicate previous and future clinical and anatomical research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female ejaculation is another fluid that has been described which occurs during orgasm. It consists of the secretion of a few milliliters of a dense and milky liquid through the urethra, being originated in the paraurethral (Skene's) glands, which are considered to be the female prostate or G spot for some authors, as it contains prostate specific antigen (PSA) [23]. However, at orgasm, another fluid can be expelled: squirting or gushing.…”
Section: Urinary Incontinence During Sexual Activitymentioning
confidence: 99%
“…Further studies should focus this aspect, with validated psychometric tools designed to examine selfperceived orgasmic intensity [72]. G-spot and CUV complex are in fact frequently associated with other sexual phenomena, such as squirting (SQ) [61,75] and female ejaculation (FE) [62,[76][77][78][79]. FE is the secretion of a few milliliters of a thick, milky fluid by the female prostate (Skene's glands) during orgasm, which contains prostatespecific antigen.…”
Section: Which Function For the G-spot? Towards A Multifactorial Explanation Of The Female Sexual Experiencementioning
confidence: 99%